Toksisitas Daun Mint (Mentha arvensis) Terhadap Larva Udang (Artemia salina Leach) - Arien Puspa Retno; Surahmaida (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Medicinal plant are part of the flora that grows and is widespread in Indonesia, one of which is mint (Mentha arvensis). Mint plant is an aromatic herbaceous plant that is widely used for air freshener, as a food garnish, and medicine. However, few studies have tested the toxicity of mint leaves. To achieve safe treatment, many studies have been carried out in pharmacological and toxicity testing of medicinal plants. The toxicity test of these medicinal plants uses the Brine Shrimp Lethality Test (BSLT) method after 24 hours of exposure to the sample being tested. This study aimed to determine the toxicity of mint leaves (Mentha arvensis) to shrimp larvae (Artemia salina Leach). Mint leaf extract was obtained from a 24-hour maceration extraction process using 96% ethanol as a solvent. Toxicity test were carried out using the Brine Shrimp Lethality Test (BSLT) method with a concentration of 1 ppm, 2 ppm, 3 ppm, 4 ppm ad 5 ppm. The percentage of deaths of shrimp larvae was calculated and calculation of LC50 value using Probit analysis. The LC50 value was obtained 3,5223 ppm and its categorized as very toxic to shrimp larvae because LC50 < 30 ppm. It can be concluded that mint leaves (Mentha arvensis) can be used as a candidate to be developed as an anti-cancer drug.